Light-Assisted Fabrication of Hierarchical Azopolymer Structures Using the Breath Figure Method and AAO Templates - Chang, Ming-Hsuan (Langmuir : the ACS journal of surfaces and colloids, 2024)
Hierarchical polymer structures have garnered widespread application across various fields owing to their distinct surface properties and expansive surface areas. Conventional hierarchical polymer structures, however, often lack postfabrication scalability and spatial selectivity. In this study, we propose a novel strategy to prepare light-assisted hierarchical polymer structures using azopolymers (PAzo), the breath figure method, and anodic aluminum oxide (AAO) templates. Initially, the breath figure PAzo films are prepared by dripping a PAzo chloroform solution onto glass substrates in a high-humidity environment. The AAO templates are then placed on the breath figure PAzo film. Upon ultraviolet (UV) light exposure, the azobenzene groups in the azopolymers undergo trans-cis photoisomerization. This process causes the glass transition temperature (Tg) of the PAzo to become lower than room temperature, allowing the azopolymer to enter the nanopores of the AAO templates. The hierarchical azopolymer structures are then formed by using a sodium hydroxide solution to remove the templates. Furthermore, exploring the effects of PAzo concentration and UV light exposure duration on the film morphology reveals optimized conditions for hierarchical structure formation. Additionally, the water contact angles of these polymer structures are measured. The hierarchical PAzo structures exhibit higher hydrophobicity compared with the flat PAzo films and the PAzo breath figure films. Finally, patterned breath figure films can be prepared using designed photomasks, demonstrating the method's capability for spatial selectivity